If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + 3 = 3(y + -7) Reorder the terms: 3 + 2y = 3(y + -7) Reorder the terms: 3 + 2y = 3(-7 + y) 3 + 2y = (-7 * 3 + y * 3) 3 + 2y = (-21 + 3y) Solving 3 + 2y = -21 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. 3 + 2y + -3y = -21 + 3y + -3y Combine like terms: 2y + -3y = -1y 3 + -1y = -21 + 3y + -3y Combine like terms: 3y + -3y = 0 3 + -1y = -21 + 0 3 + -1y = -21 Add '-3' to each side of the equation. 3 + -3 + -1y = -21 + -3 Combine like terms: 3 + -3 = 0 0 + -1y = -21 + -3 -1y = -21 + -3 Combine like terms: -21 + -3 = -24 -1y = -24 Divide each side by '-1'. y = 24 Simplifying y = 24
| 4m-8= | | (3x+1)/5=5 | | 20x-5=7+16 | | 2(3x+1)=9x | | 2x-(3x+2)=-7 | | n+(-7)-n= | | g(t)=.75t+3 | | 1.06y-3=8.62 | | 1-2c+12=-3+12-20 | | 25x+70-5x=-20.9 | | 2(3-5x)+2(x-7)=ax+b | | 12-(-u)=19 | | 7b-(2b+7)= | | 2(3+x)=2(3)+2(x) | | 3x-3x=-3x+x-3 | | 8(y-3)=4y-48 | | 1-4b-6b=-9 | | 0.25x+.05(14-x)=.10(-21) | | 1-2(c+6)=-3-4(3-5) | | 0.1x=0.2[x+2] | | -7(x+9)-(2-5x)=-13x | | [2t-3]=3t-2 | | 8b+4-2b=x-14 | | 8(2N-5)=3(5n+2) | | 8k-2(k+7)=15+6k | | (5x-4)*(5x-4)+(5x-4)=0 | | 0.07*73=0 | | 25-(x^12a)=0 | | 4x+5=(3x-1) | | 8k-2(k+7)=15 | | 8x-2x=66 | | 4a+3a-6=43 |